An updated systematic review and meta-analysis on the social determinants of diabetes and related risk factors in the Caribbean - Leonor Guariguata; Catherine Brown; Natasha Sobers; Ian Hambleton; T. Alafia Samuels; Nigel Unwin (Pan American Health Organization, 2018)
Objectives. To conduct an analysis of the most recent data on diabetes and its risk factors by gender and other social determinants of health to understand why its prevalence is higher among women than men in the Caribbean; to inform policy agenda-setting for diabetes prevention and control in the Caribbean; and to identify gaps in the evidence that require further research. Methods. A previous systematic review of the literature describing studies conducted in the Caribbean that presented the distribution of diabetes, its outcomes, and risk factors, by one or more social determinants, was updated to include sources from 1 January 2007 - 31 December 2016. Surveys by the World Health Organization (WHO) were also included. Where data were sufficient, meta-analyses were undertaken. Results. A total of 8 326 manuscripts were identified. Of those, 282 were selected for full text review, and 114, for abstraction. In all, 36 papers, including WHO-related surveys, had sufficient information for meta-analysis. More women compared to men were obese (OR: 2.1; 95%CI = 1.65 - 2.69), physically inactive (OR: 2.18; 95%CI = 1.75 - 2.72), and had diabetes (OR: 1.48; 95%CI = 1.25 - 1.76). More men smoked (OR: 4.27; 95%CI = 3.18 - 5.74) and had inadequate fruit and vegetable intake (OR: 1.37; 95%CI = 1.21 - 1.57) Conclusion. Thirty-six papers were added to the previously conducted systematic review; of those, 13 were added to the meta-analysis. Diabetes and its risk factors (primarily obesity and physical inactivity) continue to disproportionately affect women in the Caribbean. Smoking interventions should be targeted at men in this geographic area.